Surgical treatment of tubal infertility: - Marana, Riccardo; Catalano, Giovan Fiore; Muzii, Ludovico (Medicina e Morale, 1993)
Approximately 40% of cases of female infertility are due to a tubo-peritoneal factor. The main causes of tubal damage are salpingitis, pelvic inflammatory disease, previous abdominal surgery and pelvic endometriosis. Recent improvements in fertility surgery, refinements in microsurgical techniques and the introduction of operative laparoscopy have allowed for an increase in the percentage of pregnancies obtainable in these patients and, at the same time, less discomfort for the patients. The introduction of salpingoscopy has allowed to select the patients who could benefit from tubal surgery, avoiding major surgery in patients of irreversible damage of the tubal mucosa. Results obtained at microsurgery and operative laparoscopy are better than those obtained at In Vitro Fertilization-Embryo Transfer (I.V.F. - E.T.). These techniques should therefore constitute the primary approach to tubo-peritoneal pathology as a factor in female infertility.